Self-esteem - Zeigler-Hill, Virgil (New York : Psychology Press, 2013)
"In this edited collection a distinguished set of contributors present a broad overview of psychological research on self-esteem. Each chapter is written by leading experts in the field, and surveys current research on a particular issue concerning self-esteem. Together, the chapters provide a comprehensive overview of one of the most popular topics in psychology. Each chapter presents an in-depth review of particular issues concerning self-esteem, such as the connection that self-esteem has with the self-concept and psychological adjustment. A number of further topics are covered in the book, including: - How individuals pursue self-esteem - The developmental changes in feelings of self-worth over the life span. - The existence of multiple forms of high self-esteem - The role that self-esteem plays as an interpersonal signal - The protective properties associated with the possession of high self-esteem This collection of state-of-the-art reviews of key areas of the psychological literature on self-esteem will be of great interest to researchers, and academics, and also to graduate and advanced undergraduate students of social psychology"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Self-esteem.; Electronic books